Estimación del volumen de petróleo a recuperar del proceso de inyección de agua a partir de nuevas curvas de permeabilidad relativas determinadas por medio de datos de producción en el campo Apiay (2019)
The current work presents a methodology to determine new relative permeability curves through production data in the Apiay Field, located in the basin of the Llanos Orientales of Colombia, which is subject to secondary recovery by water injection specifically in the T2 unit (San Fernando Formation). With their obtaining, these curves were used in the Buckley-Leverett water injection prediction method in the Sahara software, in order to estimate the volume of oil to be recovered in three field injection patterns. In this way, it was evident that the proposed methodology to find the curves worked only for one of the three sub-layers that make up the T2 formation, where it was found that, on average, the volume of oil to be recovered calculated from the new curves Kr is 6.9, 10.5, and 196.2 times larger than the volume of oil to recover calculated from the current curves in each of the three injection patterns respectively. In this sense, the results showed that the new curves correctly described the ability of fluids to flow within the reservoir and that the methodology represents an option to reduce uncertainty in the predictions of oil to recover.